Dissemination of the Brief Alcohol Intervention in the United States Air Force: Study Rationale, Design, and Methods. (2nd January 2018) - Derefinko, Karen J.; Linde, Brittany D.; Klesges, Robert C.; Boothe, Tina; Colvin, Lauren; Leroy, Karen; Little, Melissa A.; Pasker, Christin; Murphy, James G.; McDevitt-Murphy, Meghan E.; Bursac, Zoran; Ebbert, Jon O.; et al.
ABSTRACT: This article describes a universally implemented brief alcohol intervention (BAI) administered across 4 major United States Air Force Technical Training sites for the past 6 years and plans to study the added benefit of a booster BAI session through a randomized design. The proposed BAI booster study design is described, as well as strengths and limitations of this design in light of challenges to conducting alcohol research in the U.S. military. Study outcomes include the occurrence of future alcohol-related incidents as well as cost-savings. The proposed study may provide important information regarding the value of adapting BAIs to other U.S. branches of military service in an effort to manage underage alcohol use and promote early identification of binge drinking through a large group format, and the efficacy and cost-savings potential that brief interventions have in reducing problem drinking.